Pengembangan Permainan Accounting Maze Berbasis Android Sebagai Media Pengayaan - Budiono, Erika Agustina; Rochmawati, Rochmawati (Jurnal Pendidikan Akuntansi (JPAK), 2020)
The purpose of this development research is to produce an android-based accounting maze game as an enrichment media for notes receivable which can be used as a reference for teachers as an enrichment media in order to motivate students during an enrichment process. The development model was adapted from the ADDIE development model recommended by Reiser and Mollenda through the Analysis, Design, Development, Implementation steps, but leaving the last step namely Evaluation. The results of the feasibility test from material experts and media expert in this research indicate that the android-based accounting maze game as an enrichment media obtained a very decent interpretation. In addition, the acquisition of the student response questionnaire received with a very understanding interpretation, therefore from the results of these percentages it can be concluded that the android based accounting maze game as a media of enrichment in notes receivable it stated to be very suitable for use in enrichment activities inside or outside the classroom.